1970
DOI: 10.1111/j.1095-8649.1970.tb03294.x
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to balance the energy budget of a host‐parasite system

Abstract: A quantitative assessment of the demand by the parasite Schistocephalus solidus (Miiller, 1776) upon its secondary host, GasteroJfeus aculentus L., was obtained by comparing the energy budgets for infected and non-infected fish. Observations on the energy transformations during feeding, assimilation, growth and respiration of fishes indicated some overall effects of the parasite upon host metabolism.Infection resulted in a greater depletion of host food reserws, shown by a marked increase in mortality of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
4

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 8 publications
7
89
4
Order By: Relevance
“…The crabs Hemigrapsus crenulatus, when parasitised by the acanthocephalan parasite Profilicollis antarcticus, also have a higher metabolic rate (Haye & Ojeda 1998). Several studies have indicated that parasitised fish have greater energy requirements as a result of the parasite's use of a portion of their assimilated energy stores (Walkey & Meakins 1970, Giles 1987, Godin & Sproul 1987, Lozano 1991.…”
Section: Discussionmentioning
confidence: 99%
“…The crabs Hemigrapsus crenulatus, when parasitised by the acanthocephalan parasite Profilicollis antarcticus, also have a higher metabolic rate (Haye & Ojeda 1998). Several studies have indicated that parasitised fish have greater energy requirements as a result of the parasite's use of a portion of their assimilated energy stores (Walkey & Meakins 1970, Giles 1987, Godin & Sproul 1987, Lozano 1991.…”
Section: Discussionmentioning
confidence: 99%
“…For example, under ad libitum feeding conditions, S. solidus-infected sticklebacks ingest more food than uninfected conspecifics (Walkey and Meakins, 1970) and the reduced liver size of infected sticklebacks strongly implies substantial energetic drain (Arme and Owen, 1967;Walkey and Meakins, 1970). Moreover, at low feeding levels, mortality is significantly higher for infected than non-infected sticklebacks (Pascoe and Mattey, 1977).…”
Section: The Host Immune Response Hypothesismentioning
confidence: 99%
“…Nutritional deprivation is a natural part of the life cycle of many aquatic organisms and results from winter torpor, seasonal variation of food availability, behavioral modifications during mating/spawning (Schirf et al 1987) and also parasitism (Walkey & Meakins 1970, Astete-Espinosa & Caceres 2000. Most species reduce their metabolic rate and deplete protein, carbohydrate, glycogen and/or lipid reserves during nutritional stress (Hazlett et al 1975, Regnault 1981.…”
Section: Introductionmentioning
confidence: 99%